Dukungan Sosial Keluarga, Efikasi Diri, dan Kecemasan Dapat Mempengaruhi Motivasi Belajar Siswa Saat Melakukan Pembelajaran Daring di Masa Pandemi Covid-19: Family Social Support, Self-Efficacy, And Anxiety Can Affect Student Learning Motivation When Conducting Online Learning During the Covid-19 Pandemic - Cupi Krisnawati; Nurul Ainul Shifa; Saiful Gunardi (Jurnal Interprofesi Kesehatan Indonesia, 2022)
Introduction: Students' learning motivation during online learning decreases. Objectives: This research was conducted so that students can maintain learning motivation during the online learning method during the Covid-19. Method: This research is a type of quantitative correlation research using a cross-sectional approach, the samples were taken in this study were 74 respondents. The instrument used is a questionnaire via a google form. Result: Based on the results of statistical tests, namely the Spearman rank test using SPSS, the family social support variable was obtained (p-value < 0.05) meaning that there was a correlation or relationship between family social support and learning motivation, and the self-efficacy variable was obtained (p-value < 0.05) meaning that there is a correlation or relationship between self-efficacy and learning motivation, the anxiety variable is obtained (p-value < 0.05), meaning that there is a correlation or relationship between anxiety and student learning motivation during online learning during the Covid-19 pandemic. Conclusion: Based on the research results, there is a significant relationship between family social support, self-efficacy, and student anxiety with learning motivation.